2021
DOI: 10.1200/jco.2021.39.15_suppl.5509
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bintrafusp alfa, a bifunctional fusion protein targeting TGF-β and PD-L1, in cervical cancer: Data from phase 1 and phase 2 studies.

Abstract: 5509 Background: The accelerated FDA approval of pembrolizumab validated the efficacy of anti–PD-(L)1 therapy for pts with recurrent/metastatic cervical cancer; however, the objective response rate (ORR) with pembrolizumab was 14.3% in pts with PD-L1 expressing tumors. HPV infection is implicated in > 95% of cervical cancers and is linked to upregulation of TGF-β signaling. Bintrafusp alfa is a first-in-class bifunctional fusion protein composed of the extracellular domain of the TGF-βRII receptor (a TGF-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…In contrast, anti-PD-(L)1 therapies tend to be less effective in patients with adenocarcinoma (93,102,115) and those who have been exposed to bevacizumab (37,102). Additionally, the safety profile of bintrafusp alfa in patients with heavily pretreated recurrent or metastatic cervical cancer who had disease progression with platinum-containing chemotherapy was consistent with that of anti-PD-(L)1 therapies, except for treatment-related AEs known to be associated with TGF-b inhibitors (e.g., localized skin lesions including keratoacanthomas) (94,109).…”
Section: Studies Of Combinations Of Anti-pd-(l)1 Agents With Other Ch...mentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, anti-PD-(L)1 therapies tend to be less effective in patients with adenocarcinoma (93,102,115) and those who have been exposed to bevacizumab (37,102). Additionally, the safety profile of bintrafusp alfa in patients with heavily pretreated recurrent or metastatic cervical cancer who had disease progression with platinum-containing chemotherapy was consistent with that of anti-PD-(L)1 therapies, except for treatment-related AEs known to be associated with TGF-b inhibitors (e.g., localized skin lesions including keratoacanthomas) (94,109).…”
Section: Studies Of Combinations Of Anti-pd-(l)1 Agents With Other Ch...mentioning
confidence: 84%
“…One patient had a delayed partial response after initial disease progression ( 127 ). In a post hoc pooled analysis of patients with recurrent or metastatic cervical cancer from the INTR@PID 001 study and a phase 2 single-center study (NCI 012), the ORR was 28.2% (95% CI, 15.0%-44.9%) ( 94 ). Responses to bintrafusp alfa were long-lasting, with a median DOR of 11.7 months (range, 1.4-41.2 months), and were observed irrespective of tumor histology or prior bevacizumab treatment.…”
Section: Future Treatment Options In Cervical Cancer Targeting Hpv-me...mentioning
confidence: 99%
See 1 more Smart Citation
“…Bintrafusp alfa is a first-inclass bifunctional fusion protein composed of the extracellular domain of the TGF-b-RII receptor which functions as a TGF-b 'trap' fused to an PD-L1 inhibitor. 68 Strauss et al 69 reported pooled (phase I and II) safety and efficacy of 39 patients with ICI-naive, recurrent/metastatic CC treated with this drug. The ORR was 28.2% in the all-comer population and responses occurred irrespective of tumor histology or prior bevacizumab or radiation treatment.…”
Section: Combination Trialsmentioning
confidence: 99%
“…In an evaluation of bintrafusp alfa from phase I and II trials in cervical cancer, there were single reports of grade 3 treatment-related upper-gastrointestinal hemorrhage as well as hematuria [106]. This cohort was assessed in a larger data set of HPV-related malignancies, and across 59 patients, 38 patients (64.4%) experienced treatment-emergent bleeding, with nine patients (15.3%) experiencing grade 3 bleeding events [93].…”
Section: Bleedingmentioning
confidence: 99%